The development of instructional materials on sex education for elementary school students - Rini Aryani; Citra Rosalyn Anwar; Abdul Hakim; Asnur Lidayni (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study aims to develop a picture book and to investigate its validity and practicality for elementary school students. A research and development framework was employed, utilizing the ADDIE model, which consists of three stages: analysis, design, and development. Data were collected through questionnaires and an instrument for validity testing. Product testing was conducted in two stages: (1) validity testing, which involved a subject expert, a learning media expert, and an instructional design expert and (2) practicality testing, which involved five students from a small group and 26 students from a large group. The data were then analyzed by integrating both qualitative and quantitative techniques. Results showed the following: the validity was rated by the instructional materials expert at 87%, qualifying as good, and by the instructional media expert at 98%, qualifying as very good. Meanwhile, the practicality was rated by the small group at 98% and by the large group at 96%, both qualifying as very good. These results indicate that guided inquiry-based animated video media was determined to be suitable for use in early childhood learning.